While practicing math I stumbled upon an equation that goes like this:
Solve for f(3) if 2f(x) + f(3-x) = x
This is what I managed to do with it:
2f(3) + f(0) = 3
for f(0) 2f(0) +f(3) = 0
I have the correct answer which is 2, but I don't know how to get to it. I don't understand how to get to that answer. If someone could help me with this it would be great, thanks in advance.
Solve for f(3) if 2f(x) + f(3-x) = x
This is what I managed to do with it:
2f(3) + f(0) = 3
for f(0) 2f(0) +f(3) = 0
I have the correct answer which is 2, but I don't know how to get to it. I don't understand how to get to that answer. If someone could help me with this it would be great, thanks in advance.